Sterilisasi dan Induksi Daun Muda Durian (Durio zibethinus) Dalam Medium MS Dengan Penambahan Kinetin dan IAA Secara In Vitro - Gatot Supangkat; Innaka Ageng Rineksane; Kurniawati Pamuji (Universitas Muhammadiyah Yogyakarta, 2005)
A research to study the sterilization method and application of Kinetin and IAA to induce the Durian young leaf (Durio zibethinus) in MS medium was conducted in Balai Benih Induk Hortikultura in Salaman Magelang district of Central Java started on September until December 2003. The Laboratory experiment was arranged in two phases, which were the optimation phase of sterilization and induction phase. At the first phase, the sterilization method used was the modification of Mulya (2001) method. The modification use of sterilant, vitamin C antioxidant, Alcohol 70 %, Benlate, Agrept, Tween-20 and Betadine were done to obtain effectiveness of the sterilization. Explants planted then in MS medium for two weeks. Contamination time, percentage of contamination and viabilitas (percentage of living explants) were observed then. At the second phase, the treatments were arranged in a 3 x 3 factorial completely randomized design (CRD) to observed the influence of Kinetin and IAA combination. The concentration of Kinetin observed were 2, 4, and 6 mg/I, where as the IAA concentration were 0.5, 1.0, and 1.5 mg/I. All treatments were repeated three times, with three samples on each replication. The percentage of browning explants, percentage of contaminated explants, site of contamination and percentage of explants live were observed at the end of incubation. The results showed that sterilization of Durian young leaves explants with 1 g/l deterjent for 15 minutes then by 2 g/l Benlate and Agrept for 10 minutes, then by 1 g/200 mg Vitamin C, then by Alcohol 70 % for 1 minute, then by 20% Clorox, then by 2 drip of Tween-20 for 10 minute and then by Betadine decreased the contamination down to 50 %, and this kind of sterilization was relatively better than the other kinds. Application of growth regulators were not able to induce explants growth, but stimulated callus formation at the cutting surface though, in the application of Kinetin 4 mg/1 + IAA 0,5 mg/I, Kinetin 4 mg/1 + IAA 1,5 mg/1, Kinetin 6 mg/I+ IAA 0,5 mg/1 and Kinetin 6 mg/l+IAA 1,0 mg/I.